(untitled) (Global Journal of Medical Research, 2015)
Main statements of inter-cortical osteotomy technique of the alveolar crest with its horizontal atrophy are envisioned. Criteria for patient selection for the technique utilization are presented. Some aspect of prophylaxis against postoperative adverse effects and complications are discussed.